2017
DOI: 10.1016/j.celrep.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Inhibits Liver Fatty Acid Oxidation while Unmitigated Stress Leads to Anorexia-Induced Lipolysis and Both Liver and Kidney Steatosis

Abstract: Summary The unfolded protein response (UPR), induced by endoplasmic reticulum (ER) stress, regulates the expression of factors that restore protein folding homeostasis. However, in the liver and kidney, ER stress also leads to lipid accumulation, accompanied at least in the liver by transcriptional suppression of metabolic genes. The mechanisms of this accumulation are unclear, including which pathways contribute to the phenotype in each organ. We combined gene expression profiling, biochemical assays, and unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 47 publications
7
56
0
Order By: Relevance
“…ER stress also resulted in upregulation of FGF21 via ATF4 and, as a result, increased serum FGF21 . We showed that pharmacological ER stress also inhibits hepatic fatty acid oxidation; this is likely due to genetic suppression of genes that regulate the process . This suppression is partially due to the action of CHOP.…”
Section: Regulation Of Metabolism By Hepatic Er Stressmentioning
confidence: 72%
See 1 more Smart Citation
“…ER stress also resulted in upregulation of FGF21 via ATF4 and, as a result, increased serum FGF21 . We showed that pharmacological ER stress also inhibits hepatic fatty acid oxidation; this is likely due to genetic suppression of genes that regulate the process . This suppression is partially due to the action of CHOP.…”
Section: Regulation Of Metabolism By Hepatic Er Stressmentioning
confidence: 72%
“…Although obesity elicits ER stress, it might be that overnutrition per se —i.e., taking in too many calories—causes or exacerbates hepatic ER stress independent of the associated obesity. The simple act of eating a meal after a prolonged fast is sufficient to activate the UPR in the liver in mice . This finding suggests that feeding itself perturbs hepatic ER function, though presumably this perturbation and its downstream consequences are transient.…”
Section: Pathways From Obesity To Er Stressmentioning
confidence: 99%
“…Lipid accumulation in a tissue is dependent not only on lipogenesis but also on other mechanisms, such as increased lipid deposition, decreased lipolysis and/or reduced triglyceride output (Cohen et al 2011). Tunicamycin affects several pathways contributing to the hepatic lipid accumulation, including inhibition of fatty acid oxidation (DeZwaan-McCabe et al 2017), upregulation of the very low-density lipoprotein receptor (Jo et al 2013) and inhibition of efflux of triglyceride (Qiu et al 2006, Ota et al 2008. Interestingly, while tunicamycin inhibits the mRNA expression of lipogenic genes such as Fas and Srebf1 in liver (Rutkowski et al 2008), tunicamycin treatment for either 8 h or 24 h had no significant effect on lipogenic activity (DeZwaan-McCabe et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…76,77 Conversely, more recent studies have challenged whether ER stress promotes hepatic lipogenesis. 67,[78][79][80] It has been argued that ER stress may, in fact, suppress hepatic lipogenesis. [78][79][80] In comparing the various studies exploring this issue, it is important to bear in mind that the effects of ER stress are extremely dependent on the experimental conditions employed.…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…67,[78][79][80] It has been argued that ER stress may, in fact, suppress hepatic lipogenesis. [78][79][80] In comparing the various studies exploring this issue, it is important to bear in mind that the effects of ER stress are extremely dependent on the experimental conditions employed. Moreover, the UPR is a highly dynamic signaling cascade that can have variable, and even opposing, outcomes depending on the degree and duration of ER stress.…”
Section: De Novo Lipogenesismentioning
confidence: 99%